Documenting illegal land occupancy from the air - Tushev, Nina Kantcheva; Bewick, Tom; Ellis, Cameron (Technical Centre for Agricultural and Rural Cooperation, 2016)
Unmanned aerial vehicles have the potential to empower indigenous communities to become equal partners in the efforts to safeguard their territories and natural resources.